Political Economy: Past and Future - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2003)
Political economy, radical as well as conservative, remains anchored in Newtonian cosmology. This cosmology, liberating as it was in the eighteenth and nineteenth century, has become a fetter on understanding present-day society.
Keywords: 330; methodology; postmodernism; political economy; science